Summary and Analysis of Pollutant Emission and Anti-pollution Measures at Onshore Oil and Gas Terminals in the Pearl River Basin - CAO Baojiu; LI Guancheng; SHENG Wenlong; HOU Minchi; WANG Qiabin; LIU Qin (Renmin Zhujiang)
With the continuous exploitation of marine oil and gas resources in China,onshore oil and gas terminals are increasingly important as a processing and transportation hub for oil and gas exploitation.Three onshore terminals have been built in the Pearl River Basin so far.This paper analyzes the production process,pollutant emission and its environmental impact,and anti-pollution measures of onshore terminals in the Pearl River Basin,and then summarizes the environmental protection experience of onshore terminals.The results show that the main pollutants of onshore terminals are boiler exhaust and industrial wastewater,and the pollutant emission is moderate in quantity.Utilizing self-produced natural gas as the fuel for terminal heating and power generation systems can decrease the concentration of pollutants in the boiler exhaust with a milder impact on the environment.Nonetheless,it is still required to monitor the sulfur content of natural gas and adopt the low nitrogen combustion technology to decrease the oxynitride emission.For natural gas terminals with low sewage output,sewage can be reused after advanced treatment to accomplish zero sewage emission.For crude oil terminals with high sewage output,it is recommended to conduct multi-stage oil removal and then biological treatment to meet the emission standards.